Redox regulation of cGMP-dependent protein kinase Iα in the cardiovascular system - Prysyazhna, Oleksandra; Eaton, Philip (Frontiers in Pharmacology, 2015)
Elevated levels of oxidants in biological systems have been historically referred to as “oxidative stress”, a choice of words that perhaps conveys an imbalanced view of reactive oxygen species in cell and tissues. The term stress suggests a harmful role, whereas a contemporary view is that oxidants are also crucial for the maintenance of homeostasis or adaptive signaling that can actually limit injury. This regulatory role for oxidants is achieved in part by them inducing oxidative post-translational modifications of proteins which may alter their function or interactions. Such mechanisms allow changes in cell oxidant levels to be coupled to regulated alterations in enzymatic function (i.e. signal transduction), which enables “redox signaling”. In this review we focus on the role of cGMP-dependent protein kinase Iα (PKG) disulfide dimerisation, an oxidative modification that is induced by oxidants that directly activates the enzyme, discussing how this impacts on the cardiovascular system. Additionally, how this oxidative activation of PKG may coordinate with or differ from classical activation of this kinase by cGMP will also be considered.